Perancangan Aplikasi Permainan Multiplayer Gobak Sodor Berbasis Flash Di Lingkup Jaringan Lokal - Bellia Dwi Cahya Putri; Rinta Kridalukmana; Eko Didik Widianto (Jurnal Teknologi dan Sistem Komputer, 2016)
Traditional games wa played by people from ancient time. As the culture of Indonesia which has high value of togetherness, people play ittogether with a group. From all kind of traditional games in Indonesia, there is one called Gobak Sodor that well known as traditional games from Central Java. The game of Gobak Sodor made by Adobe Flash and ActionScript as programming language has two option to play the game as singleplayer and multiplayer. Multiplayer game need a server to connected both players which used smartfoxserver 2x as the server. The game developed by adopting MDLC method with four stage such as conceptualization, design process, requirements planning, and construction. The result of this scientific writing is an application of traditional game named Gobak Sodor as the media to educate people about one of traditional game in Indonesia.